2020
DOI: 10.1111/nicc.12497
|View full text |Cite
|
Sign up to set email alerts
|

Co‐administration of multiple intravenous medicines: Intensive care nurses' views and perspectives

Abstract: Background: Co-administration of multiple intravenous (IV) medicines down the same lumen of an IV catheter is often necessary in the intensive care unit (ICU) while ensuring medicine compatibility.Aims and objectives: This study explores ICU nurses' views on the everyday practice surrounding co-administration of multiple IV medicines down the same lumen.Design: Qualitative study using focus group interviews.Methods: Three focus groups were conducted with 20 ICU nurses across two hospitals in the Thames Valley … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…An example of a tension is when a nurse is instructed to give a list of medicines that the patient cannot receive all at once, so they need to prioritise what to give first (e.g. Oduyale et al, 2020). So, the tensions or contradiction is built into the objective (or goal) of the function <administer medications>, because the patient should get all required medications, but they cannot all be given at the same time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of a tension is when a nurse is instructed to give a list of medicines that the patient cannot receive all at once, so they need to prioritise what to give first (e.g. Oduyale et al, 2020). So, the tensions or contradiction is built into the objective (or goal) of the function <administer medications>, because the patient should get all required medications, but they cannot all be given at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been applied to understand workarounds when managing the co-administration of infusions in ICU, e.g. when there are compatibility issues and inadequate venous access (Oduyale et al, 2020). We build on these examples to use FRAM to explore sources of performance variability for intravenous infusion administration in an intensive care unit (ICU) in England, focusing on sources of performance variability and underlying systems contradictions.…”
Section: Introductionmentioning
confidence: 99%
“…Resiliency in health care was another concept discussed in eight (25.8%) of the included papers 10,18,21,23,28,30,43,45 . The majority of papers in this review provide a definition or description of the FRAM by explaining activities or functions in a process and the steps necessary to operationalize the FRAM (n = 25; 80.6%) 2,7,10,20-33,35-37,40,41,43-45 . Descriptions of the FRAM in the papers included in this review are provided in Appendix III.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a recent study found that despite the use of strategies to maximise venous access, intensive care unit nurses sometimes ran out of sufficient venous access for VRIIIs. Although the use of workarounds such as prioritising infusions and swapping line of infusion was perceived as important to accomplish the task, the study claimed that these workarounds could decrease patient safety by creating new pathways to VRIIIs administration errors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%